THE ENHANCEMENT OF CHEMICAL ENGINEERING BY USING PROBLEM POSING APPROACH THROUGH LESSON STUDY ACTIVITIES - Erwin Komara Mindarta; W Widiyanti; Win Windra Irdianto (Erudio Journal of Educational Innovation, 2019)
in general, chemical engineering has the aim to direct students in understanding the basic concepts of chemical engineering, fuel, and lubricating oil in the automotive field. One of the subjects is calculating octane numbers of gasoline which involve mathematical operations, which can cause anxiety to the learner. Therefore, a learning approach is needed that can reduce mathematical anxiety through problem posing. The application of problem posing aims to improve student learning outcomes. Before being applied, lesson study (plan-do-see) was carried out. The sample consists of 32 students, with the technique of collecting observation data & pre-test & post-test. Data were analyzed descriptively and t-test. The results of the study found an  increase in learning outcomes as seen by the post-test score = 89.75 higher than the pre-test score = 78.5.